2000
DOI: 10.1046/j.1439-0434.2000.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of a Bowman–Birk‐type Trypsin Inhibitor from Wheat Kernel

Abstract: A trypsin inhibitor from wheat kernel (WTI) was found to have a strong antifungal activity against a number of pathogenic fungi and to inhibit fungal trypsin‐like activity. WTI inhibited in vitro spore germination and hyphal growth of pathogens, with protein concentration required for 50% growth inhibition (IC50) values ranging from 111.7 to above 500 μg/ml. As observed by electron microscopy, WTI determined morphological alterations represented by hyphal growth inhibition and branching. One of the fungal spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 27 publications
2
37
0
1
Order By: Relevance
“…The results of the study of Chen et al (25) revealed that the resistance of certain corn genotypes to fungal infection might be related to the action of trypsin inhibitor in lowering the production of fungal ␣-amylase and its activity and consequently reducing the availability of simple sugars for fungal growth. A trypsin inhibitor from wheat kernel also elicited a potent antifungal BIOCHEMICAL AND BIOPHYSICAL RESEARCH COMMUNICATIONS effect (26). A 28-kDa alkaline protease inhibitor from Streptomyces (27), a 24-kDa cysteine protease inhibitor from pearl millet (28), and the HIV-1 protease inhibitors (29) exhibited antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study of Chen et al (25) revealed that the resistance of certain corn genotypes to fungal infection might be related to the action of trypsin inhibitor in lowering the production of fungal ␣-amylase and its activity and consequently reducing the availability of simple sugars for fungal growth. A trypsin inhibitor from wheat kernel also elicited a potent antifungal BIOCHEMICAL AND BIOPHYSICAL RESEARCH COMMUNICATIONS effect (26). A 28-kDa alkaline protease inhibitor from Streptomyces (27), a 24-kDa cysteine protease inhibitor from pearl millet (28), and the HIV-1 protease inhibitors (29) exhibited antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Another three genes induced by aluminum in wheat (wali3, wali5 and wali6) have also been found to be similar to some sugarcane genes. These wheat genes encode Bowman-Birk type trypsin inhibitors, an extensively studied family of protease inhibitors (Laskowsky and Kato, 1980), whose homologs in soybean have been shown to have antifungal activity (Chilosi et al, 2000) and have been suggested to be a defense against insect feeding (Belzunces et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…3 BowmaneBirk inhibitors (BBIs) typically comprise 60e90 amino acids, and perform dual inhibition of trypsin-and/or chymotrypsin-like proteases via disulfide-bonded b-hairpin loop motifs, which bind at catalytic sites via canonical protease recognition sequences. 4,5 In the early 1990s it was demonstrated that synthetic peptide mimics of the BBI b-hairpin loop motif retain biological activity.…”
Section: Introductionmentioning
confidence: 99%